Platonopolis : Platonic political philosophy in late antiquity - O'Meara, Dominic J. (Clarendon Press ; Oxford University Press, 2003)
Conventional wisdom suggests that the Platonist philosophers of late antiquity, from Plotinus (3rd century) to the 6th-century schools in Athens and Alexandria, neglected the political dimension of their Platonic heritage in concentrating on an otherworldly life. The author presents a reappraisal.